Diagnostic and therapeutic challenges in a child with complete interferon‐γ receptor 1 deficiency. Issue 11 (14th July 2015) - Olbrich, Peter; Martínez‐Saavedra, Maria Teresa; Perez‐Hurtado, José Maria; Sanchez, Cristina; Sanchez, Berta; Deswarte, Caroline; Obando, Ignacio; Casanova, Jean‐Laurent; Speckmann, Carsten; Bustamante, Jacinta; Rodriguez‐Gallego, Carlos; Neth, Olaf
<x xml:space="preserve">Abstract</x> Autosomal recessive (AR) complete Interferon‐γ Receptor1 (IFN‐γR1) deficiency is a rare variant of Mendelian susceptibility to mycobacterial disease (MSMD). Although hematopoietic stem cell transplantation (HSCT) remains the only curative treatment, outcomes are heterogeneous; delayed engraftment and/or graft rejection being commonly observed. This case report and literature review expands the knowledge about this rare but potentially fatal pathology, providing details regarding diagnosis, antimicrobial treatment, transplant performance, and outcome that may help to guide physicians caring for patients with AR complete IFN‐γR1 or IFN‐γR2 deficiency. Pediatr Blood Cancer © 2015 Wiley Periodicals, Inc.